Entrepreneurial opportunities - Eckhardt, Jon (Henry Stewart Talks, 2012)
The entrepreneurial process, Definition of opportunity, Characteristics of entrepreneurial opportunities, Why consider opportunities?, Opportunities: central to entrepreneurial process, Opportunities influence the outcomes, Sources of opportunities: external change & internal change, Forms of opportunities, What makes a good opportunity?, Suitability for new ventures, Start-up vs. Established producer
Reviewed at 2020/01/30